2016
DOI: 10.29333/iejme/315
|View full text |Cite
|
Sign up to set email alerts
|

Professional Pedagogical Education Quality Management

Abstract: The urgency of the issue stated in this article is caused by the need for effective educational practice in the effective management mechanisms of professional pedagogical education quality, which consider the specificity of educational process of teachers training and consistency of personal development of the future teacher. The aim of the article is to develop and describe the design principles of management system of personal-oriented pedagogical education quality in higher school. The leading method of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Rural schools are those located in Zvecan, Zubin Potok, Socanica, Leposavic and Lesko, which are not too far behind the northern part of Kosovska Mitrovica in terms of urbanity. On the other hand, there are studies which determined students from rural primary schools showed greater interest in physical exercise and sports precisely due to the lack of opportunities, compared to students from urban primary schools (Gabdrakhmanova & Kostarev, 2016). The aforementioned fact Zamijeniti s: is in line with the research findings of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Rural schools are those located in Zvecan, Zubin Potok, Socanica, Leposavic and Lesko, which are not too far behind the northern part of Kosovska Mitrovica in terms of urbanity. On the other hand, there are studies which determined students from rural primary schools showed greater interest in physical exercise and sports precisely due to the lack of opportunities, compared to students from urban primary schools (Gabdrakhmanova & Kostarev, 2016). The aforementioned fact Zamijeniti s: is in line with the research findings of this study.…”
Section: Discussionsupporting
confidence: 88%
“…The shift to the implementation of SCL extends the role of educational technology. Educational technology is an important part of the innovative development of professional education [3]- [7]. A studentcentered classroom is a place where teachers understand the needs of the students and allow them to engage all the time in the learning process.…”
Section: Introductionmentioning
confidence: 99%